New Horizons of Process Chemistry Scalable Reactions and Technologies - Tomioka, Kiyoshi; Shioiri, Takayuki; Sajiki, Hironao; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The methodologies and technologies adaptable to process chemistry are the focus of this unique book, as new catalysts, reactions, and methods for the synthesis of functional materials are dealt with in depth for the first time. Those materials take in pharmaceuticals, agrochemicals, functional materials, chemical raw materials, and other substances in the field of process chemistry including green chemistry. Process chemistry underpins the competitiveness of chemical and pharmaceutical industries, but its stagnation is estimated to cause industrial depression and excessive loss. For that reason, chemists focus on process chemistry consistently so that the development of novel and efficient new reactions and technologies provides an essential stimulus. In addition, this volume describes the important development of selected new synthetic devices for process development and the process design for a larger scale, thus furnishing a valuable source for all who are engaged in process chemistry. .
Recent Advances in Rare Earth Metal Asymmetric Catalysis Toward Practical Synthesis of Therapeutics -- Metal Catalyzed Synthetic Reactions via Aerobic Oxidation as a Key Step -- Heterogeneous Platinum Metal Catalyzed Deuterium Generation and Labeling Methods Using Hydrogen Gas and Deuterium Oxide as Key Reagents -- Pd on Spherical Carbon (Pd/SC)-Catalyzed Chemoselective Hydrogenation -- Environment-Friendly Iron-Catalyzed Reactions -- Tetranuclear Zinc Cluster-Catalyzed Transesterification -- Vinyl Ruthenium Carbenes: Valuable Intermediates in Catalysis -- Radical-based Late Stage C-H Functionalization of Heteroaromatics in Drug Discovery -- Magnetic Nanoparticle-Supported Iodoarene Oxidative Catalyst and its Application to Phenol Oxidation -- Recent Development of Diphenyl Phosphorazidate (DPPA) as a Synthetic Reagent -- Methylenation Reaction of Carbonyl Compounds Using Julia-Kocienski Reagents -- Development of Shelf-stable Reagents for Electrophilic Trifluoromethylthiolation Reaction -- Practical and Environmentally Friendly Transformation of Tetrahydrofuran-2-methanols to γ-Lactones via Oxidative Cleavage.-　Five Step Asymmetric Total Synthesis of β-Lycorane Employing Chiral Diether Ligand-controlled Conjugate Addition-Michael Reaction Cascade.-　Concise Synthesis of Peptide Analogs Using a Fluorous-Fmoc Protection Strategy -- A Challenging Synthesis of the Highly Functionalized Echinocandin ASP9726: A Successor of Micafungin - How Can We Achieve the Large-Scale Synthesis?- The Role of Silyl Protecting Group for the Synthesis of Procyanidins and Their Derivatives -- Chemical Modification of the 3'-Dangling End of Small Interfering RNAs such as siRNAs and miRNAs: the Development of miRNA Replacement Therapy -- Antiviral Agents towards Chikungunya Virus: Structures, Syntheses, and Isolation from Natural Sources -- Analytical Standards Purity Determination Using Quantitative Nuclear Magnetic Resonance.
Keywords: Chemistry, Technical; Chemistry, Organic; Pharmacy; Agriculture; Catalysis; Industrial Chemistry; Organic Chemistry; Pharmacy; Agriculture; Catalysis